2003
DOI: 10.1159/000067111
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Temporal Distribution of Mortality Rates for Multiple Sclerosis in Canada, 1965–1994

Abstract: Statistics Canada data were used to calculate multiple sclerosis (MS) mortality rates per 100,000 population in the Canadian provinces from 1965 to 1994. For the period 1965–1994, the highest average annual MS mortality rates were in Quebec (4.4) and Ontario (3.9), while the Western Provinces had an intermediate rate (2.1) and the Atlantic Provinces had the lowest rate (1.2). Female mortality rates exceeded male rates in each of the four regions. Average annual MS mortality rates in Canada overall fluctuated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…This contrasts with a recent study of US national mortality data which found increased mortality between 1990 and 2001 [23]. In other countries, such as Canada, rates have been reported to fluctuate over time rather than show a directional trend [29]. We found no evidence of either a rise or decline in the Oxford region overall, from 1979 to 2006.…”
Section: Multiple Sclerosiscontrasting
confidence: 99%
“…This contrasts with a recent study of US national mortality data which found increased mortality between 1990 and 2001 [23]. In other countries, such as Canada, rates have been reported to fluctuate over time rather than show a directional trend [29]. We found no evidence of either a rise or decline in the Oxford region overall, from 1979 to 2006.…”
Section: Multiple Sclerosiscontrasting
confidence: 99%
“…Moreover, some papers have identified a lack of correlation between prevalence and mortality distribution [13], probably due to differences in health care or disease severity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Like other presumed autoimmune diseases, MS is more common in females and clinical symptoms often appear during young adulthood [21]. Patients with MS show relatively high morbidity and mortality rates, especially in chronic progressive forms of the disease and particularly among those living in high latitudes [22,23], both in the northern and southern hemispheres.…”
Section: Discussionmentioning
confidence: 99%